THE RHIZOSPHERE PGPR GRAMINEAE APPLICATION ON THE GROWTH RED GINGER (Zingiber officinale Var. Rubrum) - Hesti Kurniahu (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2017)
PGPR (Plant Growth Promoting Rhizobacteria) is a group of bacteria that colonize in the area of the rhizosphere. These groups of bacteria favor plant growth because they are able to mobilize and provide nutrients and phytohormones. The ability of the bacterial group can be utilized as a growth regulator in the red ginger nursery (Z. officinale Var Rubrum). This study aims to determine the optimal dosage of PGPR for the growth of red ginger seed (Z. officinale Var Rubrum). In this study, red ginger rhizome (Z. officinale Var Rubrum) was soaked with various concentrations of PGPR ie 0%, 25%, 50%, 75% and 100%. The results of this study indicate that soaking rhizomes using PGPR solution significantly influence the growth of red ginger seeds in the form of high seedlings, the number of shoots grow, the number of leaves and the mass of seedlings. A 25% dose has a better ability to boost the growth of seeds when compared to other doses.Keywords: Zingiber officinale Var. Rubrum, PGR, Phytohormone.